Educação Literária e formação de leitores: da leitura 'em si' para leitura 'para si' - Souza, Renata Junqueira de [UNESP]; Girotto, Cyntia Graziella Guizelim Simões [UNESP]; Silva, Joice Ribeiro Machado da [UNESP] (My University, 2012)
This article deals with the relationship between the reader formation and the teaching of strategies of reading. We based our discussion in reading and childhood literature researchers as: Arena (2007a, 2007b, 2008 and 2010), Bajard (2002), Chiappini (1997), Coelho (2000), Cosson (2007), Foucambert (1994), Harvey & Goudivs (2007), Perroti (1986), Smith (1999), Soares (1999), Solé (2009), Zilberman (2005), and others. We dialogue with some points from the historical-cultural perspective, having a strong focus on a humanitarian literary education in elementary schools.

O artigo trata da relação entre a formação de leitores e abordagem do ensino das estratégias de leitura. Com base em estudiosos da leitura e da literatura infantil, como Arena (2007a, 2007b, 2008 e 2010), Bajard (2002), Chiappini (1997), Coelho (2000), Cosson (2007), Foucambert (1994), Harvey & Goudivs (2007), Perroti (1986), Smith (1999), Soares (1999), Solé (2009), Zilberman (2005), dentre outros, faz-se um diálogo com alguns dos pressupostos da perspectiva histórico cultural, tendo como foco uma educação literária humanizadora, no ensino fundamental, a partir dessa possível aproximação teórico-metodológica.
Literary education and a task to build readers: the reading in it to the reading through it